The Role of Field Education in a University–Community Partnership Aimed at Curriculum Transformation. (2nd April 2016) - Lewis, Laura A.; Kusmaul, Nancy; Elze, Diane; Butler, Lisa
ABSTRACT: University–community partnerships can play an important role in curriculum development, but little has been written about the role of community agencies in designing curricula. This article describes the role of field education in an innovative university–community partnership aimed at transforming an MSW curriculum to integrate a trauma-informed and human rights perspective throughout foundation- and advanced-year courses. This university–community partnership positioned field educators and social service agencies in a collaborative relationship with faculty in curriculum development. The benefits and potential challenges associated with employing a university–community partnership for curriculum change are discussed, and recommendations are provided for schools that are interested in using this approach.